2021
DOI: 10.1016/j.irfa.2021.101958
|View full text |Cite
|
Sign up to set email alerts
|

“Shiny” crypto assets: A systemic look at gold-backed cryptocurrencies during the COVID-19 pandemic

Abstract: In this paper, we empirically analyse the performance of five gold-backed stablecoins during the COVID-19 pandemic and compare them to gold, Bitcoin and Tether. In the digital assets' ecosystem, gold-backed cryptocurrencies have the potential to address regulatory and policy concerns by decreasing volatility of cryptocurrency prices and facilitating broader cryptocurrency adoption. We find that during the COVID-19 pandemic, gold-backed cryptocurrencies were susceptible to volatility transmitted from gold marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Cryptocurrencies are considered riskier as any central body does not regulate them. Higher technical knowledge and awareness can minimize perceived risk and mediate the positive relationship between technology awareness and consumers' behavioral intention (Jalan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptocurrencies are considered riskier as any central body does not regulate them. Higher technical knowledge and awareness can minimize perceived risk and mediate the positive relationship between technology awareness and consumers' behavioral intention (Jalan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…People are afraid of embracing new technology for various reasons, while the most common is the level of uncertainty (Lim, 2003;Mizanur and Sloan, 2017). Jalan et al (2021) defined risk as a knowledge of the degree of insecurity used to consider investors' or customers' decisions to adopt a technology (Slovic et al, 1982;Anser et al, 2020). Moreover, perceived risk was a crucial factor in using and adopting technology.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from the quantile regression results that a decrease in gold volatility under average and extreme market conditions changes the value of ETF. Jalan et al (2021) empirically tested the role of five gold-backed cryptocurrencies and gold against equities during the pandemic. They found that gold-backed cryptocurrencies do not show safe haven property like gold.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies show the relationship between cryptocurrencies is strong (Bouri et al, 2021;Moratis, 2021;Zhang & Mani, 2021;Naeem et al, 2021), and cryptocurrencies are related with global events (Wang et al, 2020b;Nguyen et al, 2022), also positive and negative shocks have different effects on cryptocurrencies (Fakhfekh & Jeribi, 2020;Zhang & Mani, 2021). In addition, some of the studies analyzed (Huynh, 2020;Jalan et al, 2021) revealed that stablecoins are volatile, meaning they are not stable. Therefore, the lack of consensus on the relationship between stablecoins and cryptocurrencies makes it essential to examine and study the subject.…”
Section: International Journal Of Economic and Administrative Studiesmentioning
confidence: 99%